"I simply don't know, because I don't know which drugs I get": Perspectives on deprescribing among older adults with limited life expectancy and their relatives. Issue 1 (28th August 2020) - Graabæk, Trine; Lundby, Carina; Ryg, Jesper; Søndergaard, Jens; Pottegård, Anton; Nielsen, Dorthe Susanne
Abstract: Use of medications of questionable benefit is common in end of life care. In order to effectively carry out deprescribing, it is important to gain insight into the perspectives of patients and their relatives. Thus, our objective was to explore perspectives on deprescribing among older adults with limited life expectancy and their relatives. We conducted semi‐structured interviews with ten nursing home residents and nine relatives. Interviews were analysed using systematic text condensation. Four main themes were identified: "Medication as a necessity and to feel well, " "Frailty as a barrier for taking responsibility, " "Patient autonomy and faith in authority" and "A wish for being involved." Most participants had not considered the possibility of deprescribing but were open towards medication change if proposed by a healthcare professional. Most participants did not have in‐depth knowledge about medication but would like to be informed or involved in decisions. The participants generally had faith in healthcare professionals despite limited contact. Our study implies that older adults with limited life expectancy and their relatives are generally interested in deprescribing activities; however, the initiative of deprescribing lies with the healthcare professionals.